KUALITAS PELAYANAN PADA PT. MIXUE CABANG KARANG TENGAH KABUPATEN SUKABUMI - Firman, Arief; Rahmawati, Rahmawati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The study aims to explore in-depth information about the level of service quality provided by PT. Mixue which is located in the Central Karang Branch, Sukabumi Regency. In this study, not only service quality is the main focus, but also to identify various obstacles that may be faced in the process of providing services to consumers. Furthermore, this study also aims to offer pragmatic solutions to the challenges found during the service process. To achieve this goal, the authors adopted a methodological approach consisting of a combination of descriptive and quantitative research. In particular, this research relies on the collection of comprehensive and objective data regarding the reality that occurs in the field, which is then analyzed with reference to relevant theories or concepts. The results of the data processing are expected to provide a clear and accurate picture of the service conditions currently provided by PT. Mixue at the Karang Tengah Branch, as well as allowing the development of appropriate strategies to overcome existing problems and improve service quality in the future.